PENGARUH PENERAPAN TATA KELOLA PERUSAHAAN TERHADAP RISIKO KREDIT MELALUI RASIO KECUKUPAN MODAL PADA BANK UMUM - DWI PUSPITASARI, HESTI (Jurnal Ilmu Manajemen (JIM), 2015)
Abstract: The purpose of this study was to determine the direct or indirect effect of good corporate governance (GCG) to the non performing loan (NPL) through the capital adequacy ratio (CAR) in commercial bank. The data used are secondary data obtained from the annual reports published by each bank. Methods used in determining the amount of the sample using purposive sampling method , and then performed classical assumption on the data using path analysis as an analytical instrument. The result show that GCG have a direct effect on NPL. GGC and CAR had not effect on NPL. Thus GCG has no effect on NPL indirectly, and CAR variable can not be used as mediating variable. Keywords: good corporate governance, non performing loan, and capital adequacy ratio.